2021
DOI: 10.3390/min11121349
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Microorganisms in the Formation, Dissolution, and Transformation of Secondary Minerals in Mine Rock and Drainage: A Review

Abstract: Mine waste rock and drainage pose lasting environmental, social, and economic threats to the mining industry, regulatory agencies, and society as a whole. Mine drainage can be alkaline, neutral, moderately, or extremely acidic and contains significant levels of sulfate, dissolved iron, and, frequently, a variety of heavy metals and metalloids, such as cadmium, lead, arsenic, and selenium. In acid neutralization by carbonate and silicate minerals, a range of secondary minerals can form and possibly scavenge the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 206 publications
(265 reference statements)
0
2
0
Order By: Relevance
“…Liu et al [ 47 ] also found that with the formation of secondary Fe minerals with a mixed schwertmannite and jarosite, total Fe precipitation efficiency increased. According to previous research, the pH value and pH gradient between the surface of the mineral and the surrounding aqueous solution are key factors affecting the formation and phase transformation of secondary minerals [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Liu et al [ 47 ] also found that with the formation of secondary Fe minerals with a mixed schwertmannite and jarosite, total Fe precipitation efficiency increased. According to previous research, the pH value and pH gradient between the surface of the mineral and the surrounding aqueous solution are key factors affecting the formation and phase transformation of secondary minerals [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the mica schist, sulfur occurs mainly in pyrrhotite [Fe (1–x) S] and more rarely in pyrite (FeS 2 ) and chalcopyrite (CuFeS 2 ) ( Västi, 2011 ). Moreover, sulfides in rocks may be leached by the saline groundwater (Na + and Cl – ), oxidized in anoxic conditions abiotically with ferric iron Fe (III) or by microorganisms, and released as sulfate or other intermediate sulfur species ( Müller and Regenspurg, 2017 ; Jakus et al, 2021 ; Bao et al, 2022 ), which is evident in the recent reviews on sulfide mineral–microbe interactions ( Bomberg et al, 2021 ; Ortiz-Castillo et al, 2021 ; Spietz et al, 2022 ). Rock surface biofilms could potentially facilitate interactions in the necessary cycling processes between different groups of microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…The formation process of carbonate minerals under the action of microorganisms is relatively complex, and the mineralization results are diverse. It is not only related to the types of microorganisms, but it is also closely related to environmental conditions such as Mg/Ca ratio, pH, saturation, types and concentrations of biomolecules, and impurity ions [23][24][25].…”
Section: Introductionmentioning
confidence: 99%